Virus-Like Particle (VLP) Plus Microcrystalline Tyrosine (MCT) Adjuvants Enhance Vaccine Efficacy Improving T and B Cell Immunogenicity and Protection against Plasmodium berghei/vivax - Gustavo Cabral-Miranda; Matthew D. Heath; Mona O. Mohsen; Ariane C. Gomes; Paul Engeroff; Amy Flaxman; Fabiana M. S. Leoratti; Aadil El-Turabi; Arturo Reyes-Sandoval; Murray A. Skinner; Matthias F. Kramer; Martin F. Bachmann (Vaccines, 2017)
Vaccination is the most effective prophylactic tool against infectious diseases. Despite continued efforts to control malaria, the disease still generally represents a significant unmet medical need. Microcrystalline tyrosine (MCT) is a well described depot used in licensed allergy immunotherapy products and in clinical development. However, its proof of concept in prophylactic vaccines has only recently been explored. MCT has never been used in combination with virus-like particles (VLPs), which are considered to be one of the most potent inducers of cellular and humoral immune responses in mice and humans. In the current study we assessed the potential of MCT to serve as an adjuvant in the development of a vaccine against malaria either alone or combined with VLP using Plasmodium vivax thrombospondin-related adhesive protein (TRAP) as a target antigen. We chemically coupled PvTRAP to VLPs derived from the cucumber mosaic virus fused to a universal T-cell epitope of the tetanus toxin (CMVtt), formulated with MCT and compared the induced immune responses to PvTRAP formulated in PBS or Alum. The protective capacity of the various formulations was assessed using Plasmodium berghei expressing PvTRAP. All vaccine formulations using adjuvants and/or VLP increased humoral immunogenicity for PvTRAP compared to the antigen alone. The most proficient responder was the group of mice immunized with the vaccine formulated with PvTRAP-VLP + MCT. The VLP-based vaccine formulated in MCT also induced the strongest T cell response and conferred best protection against challenge with recombinant Plasmodium berghei. Thus, the combination of VLP with MCT may take advantage of the properties of each component and appears to be an alternative biodegradable depot adjuvant for development of novel prophylactic vaccines.